The Midcoast Regional Theater: Wiscasett, Maine - Joseph Sirkovich (Oz, 1984)
Located on the southern edge of Wiscasette, Maine, overlooking the Shepscott River, the Midcoast Regional Theater is a response to the requirement for a major performing arts facility…